Perceptions and Acceptability of Short Message Services Technology to Improve Treatment Adherence amongst Tuberculosis Patients in Peru: A Focus Group Study - Albino, Sandra; Tabb, Karen M.; Requena, David; Egoavil, Miguel; Pineros-Leano, Maria F.; Zunt, Joseph R.; García, Patricia J. (PloS one, 2014)
Tuberculosis (TB) is global health concern and a leading infectious cause of mortality. Reversing TB incidence and disease-related mortality is a major global health priority. Infectious disease mortality is directly linked to failure to adhere to treatments. Using technology to send reminders by short message services have been shown to improve treatment adherence. However, few studies have examined tuberculosis patient perceptions and attitudes towards using SMS technology to increase treatment adherence. In this study, we sought to investigate perceptions related to feasibility and acceptability of using text messaging to improve treatment adherence among adults who were receiving treatment for TB in Callao, Peru. We conducted focus group qualitative interviews with current TB positive and non-contagious participants to understand the attitudes, perceptions, and feasibility of using short message service (SMS) reminders to improve TB treatment adherence. Subjects receiving care through the National TB Program were recruited through public health centers in Ventanilla, Callao, Peru. In four focus groups, we interviewed 16 patients. All interviews were recorded and transcribed verbatim. Thematic network analysis and codebook techniques were used to analyze data. Three major themes emerged from the data: limits on health literacy and information posed challenges to successful TB treatment adherence, treatment motivation at times facilitated adherence to TB treatment, and acceptability of SMS including positive perceptions of SMS to improve TB treatment adherence. The majority of patients shared considerations about how to effectively and confidentially administer an SMS intervention with TB positive participants. The overall perceptions of the use of SMS were positive and indicated that SMS technology may be an efficient way to transmit motivational texts on treatment, health education information, and simple reminders to increase treatment adherence for low-income TB patients living in Peru.